2015
DOI: 10.1001/jamapediatrics.2015.1413
|View full text |Cite
|
Sign up to set email alerts
|

Substance Abuse and Other Adverse Outcomes for Military-Connected Youth in California

Abstract: IMPORTANCE Military families and military-connected youth exhibit significant strengths; however, a sizeable proportion of these families appear to be struggling in the face of war-related stressors. Understanding the consequences of war is critical as a public health concern and because additional resources may be needed to support military families. OBJECTIVE To determine whether rates of adverse outcomes are higher for military-connected adolescents during war compared with nonmilitary peers. DESIGN, SETTIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 37 publications
2
50
2
1
Order By: Relevance
“…That is, it appears that older teens may be suppressing the initiation of drug use during parental deployment, and then catching up with their peers who have begun to use drugs during a similar period of time, ending up similar at the end of the study. This finding is somewhat contrary to recent information from a cross-sectional study of teens in military and nonmilitary families in California, which showed higher rates of drug use among the military-affiliated teens (Sullivan et al, 2015). It is possible that our short time frame partly explains this difference.…”
Section: Discussioncontrasting
confidence: 99%
“…That is, it appears that older teens may be suppressing the initiation of drug use during parental deployment, and then catching up with their peers who have begun to use drugs during a similar period of time, ending up similar at the end of the study. This finding is somewhat contrary to recent information from a cross-sectional study of teens in military and nonmilitary families in California, which showed higher rates of drug use among the military-affiliated teens (Sullivan et al, 2015). It is possible that our short time frame partly explains this difference.…”
Section: Discussioncontrasting
confidence: 99%
“…While there were no rural‐urban differences in parental monitoring, it is important to consider parental monitoring given the extended working hours and shift work inherent in the mining occupation. We also found that alcohol use was consistently higher among adolescents with military family involvement, supporting previous research . Military family involvement did not account for higher levels of substance use reported by youth living in rural mining counties; however, the military shares many similarities to the rural mining industry in terms of its male dominated culture and the potential influence that it can have on adolescent alcohol and tobacco use behaviors .…”
Section: Discussionsupporting
confidence: 82%
“…Analysis of the 2013 California Healthy Kids Survey conducted in most school districts throughout California demonstrated higher odds of being in a fight among military-connected youth compared with their nonmilitary-connected peers (Sullivan et al, 2015). Analysis of the 2013 California Healthy Kids Survey conducted in most school districts throughout California demonstrated higher odds of being in a fight among military-connected youth compared with their nonmilitary-connected peers (Sullivan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the 2013 California Healthy Kids Survey conducted in most school districts throughout California demonstrated higher odds of being in a fight among military-connected youth compared with their nonmilitary-connected peers (Sullivan et al, 2015). For example, despite the known association between substance use and physical violence (Baskin-Sommers & Sommers, 2006;Boles & Miotto, 2003;Ellickson, Saner, & McGuigan, 1997;Harrison, Erickson, Adlaf, & Freeman, 2001;Hoaken & Stewart, 2003), as well as the demonstrated increase in substance use among adolescents from military families (Acion et al, 2013;Gilreath et al, 2013;Reed et al, 2011;Sullivan et al, 2015), only one study controlled for the confounding effect of substance use (Reed et al, 2014). While these studies suggest a potential association between family military involvement and physical fighting among adolescents, control for potentially important confounding factors is lacking.…”
Section: Introductionmentioning
confidence: 99%